Youthizen Political Literacy: Educating The Generation Z - Lailiyah, Nuriyatul; Pradhana, Ghozian Aulia; Yuliyanto, Muchammad (JURNAL ILMU SOSIAL, 2020)
This study aims to investigate the differences in attitudes of young generation in showing their political expression on social media before and after the socialization in community service. The issue is related to the attitude of young generation in using social media as a means of expres-sion. Meanwhile, we realize that the internet can often be misleading with the abundance of in-formation and hoaxes. It requires the user’s ability to choose and filter the correct and useful information. As the generation that dominates social media and the internet, Generation Z is al-so a target of politicians and political issues on the internet. Therefore, political literacy for young generation in the internet is crucial. The data in this research were collected by quantita-tive descriptive methods through surveys before and after the socialization of social media and politics. The survey was conducted on 100 high school students in Semarang City. The results showed that the program for political literacy socialization increased the political literacy of the high school students by providing a positive knowledge regarding politics. The results showed that the program increased the high school students’ political literacy and attitude towards the use of social media for political expression.